Genome-Wide Identification and Analysis of the Phosphoenolpyruvate Carboxylase Gene Family in Suaeda aralocaspica, an Annual Halophyte With Single-Cellular C4 Anatomy - Cao, Jing; Cheng, Gang; Wang, Lu; Maimaitijiang, Tayier; Lan, Haiyan (Frontiers in Plant Science, 2021)
Phosphoenolpyruvate carboxylase (PEPC) plays pivotal roles in the carbon fixation of photosynthesis and a variety of metabolic and stress pathways. Suaeda aralocaspica belongs to a single-cellular C4 species and carries out a photosynthetic pathway in an unusually elongated chlorenchyma cell, which is expected to have PEPCs with different characteristics. To identify the different isoforms of PEPC genes in S. aralocaspica and comparatively analyze their expression and regulation patterns as well as the biochemical and enzymatic properties in this study, we characterized a bacterial-type PEPC (BTPC; SaPEPC-4) in addition to the two plant-type PEPCs (PTPCs; SaPEPC-1 and SaPEPC-2) using a genome-wide identification. SaPEPC-4 presented a lower expression level in all test combinations with an unknown function; two SaPTPCs showed distinct subcellular localizations and different spatiotemporal expression patterns but positively responded to abiotic stresses. Compared to SaPEPC-2, the expression of SaPEPC-1 specifically in chlorenchyma cell tissues was much more active with the progression of development and under various stresses, particularly sensitive to light, implying the involvement of SaPEPC-1 in a C4 photosynthetic pathway. In contrast, SaPEPC-2 was more like a non-photosynthetic PEPC. The expression trends of two SaPTPCs in response to light, development, and abiotic stresses were also matched with the changes in PEPC activity in vivo (native) or in vitro (recombinant), and the biochemical properties of the two recombinant SaPTPCs were similar in response to various effectors while the catalytic efficiency, substrate affinity, and enzyme activity of SaPEPC-2 were higher than that of SaPEPC-1 in vitro. All the different properties between these two SaPTPCs might be involved in transcriptional (e.g., specific cis-elements), posttranscriptional [e.g., 5′-untranslated region (5′-UTR) secondary structure], or translational (e.g., PEPC phosphorylation/dephosphorylation) regulatory events. The comparative studies on the different isoforms of the PEPC gene family in S. aralocaspica may help to decipher their exact role in C4 photosynthesis, plant growth/development, and stress resistance.